Estimating food availability and self-reliance in island territories: Puerto Rico as a case study - Bezares, Nayla; Fisher, Chad; Ramos-Gerena, Carol E.; Suarez-Gomez, William; Cash, Sean B.; Nemecek, Thomas; Blackstone, Nicole Tichenor (Frontiers in Nutrition, 2025)
IntroductionIn Small Island Developing States (SIDS), limited statistical capacity and reliance on imports hinder comprehensive assessments of food systems. For island territories, this issue is more pronounced as food production data are disaggregated, inconsistent, and scarce. Most non-independent territories within the SIDS designation are not included in international food availability datasets, and local datasets are not readily available. Increased food self-reliance has been proposed to enhance food nutrition security and sovereignty across SIDS. Puerto Rico, an island territory of the United States, is highly reliant on food imports.MethodsUsing local import, export, and production records from fiscal years 2017–2019, combined with representative food loss and waste estimates, we developed datasets quantifying food availability and self-reliance metrics for Puerto Rico as a case study. A novel data crosswalk, adaptable to other island territories, supports the replication of this approach.ResultsOils, grains, and protein foods had the highest per-capita availability. Agricultural self-reliance was highest for dairy (95%), fruits (47%), and vegetables (33%). Food self-reliance, incorporating processed foods, was highest for dairy (70%), and vegetables (22%). Dietary self-reliance, comparing local production to dietary recommendations, was less than 20% across food groups. Loss-adjusted availability fell short of dietary recommendations for fruits and vegetables but exceeded recommended levels for grains, oils, and protein foods.DiscussionThese findings highlight critical gaps in local food production and inform strategies to align availability with nutritional goals. This approach and its metrics can be instrumental for other island territories, offering an approach to monitoring self-reliance in non-independent contexts.